2022
DOI: 10.1108/oir-08-2021-0440
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of e-government use during the COVID-19 pandemic: the case of Vietnam

Abstract: PurposeThe COVID-19 pandemic has disrupted various systems that drove people to adapt to certain technologies, such as electronic government services, for daily survival and to meet social distancing requirements. Therefore, this study aims to determine the antecedents of e-government use based on prospect theory and modified unified theory of acceptance use of technology (UTAUT) during a pandemic.Design/methodology/approachConvenience sampling of 368 respondents from Vietnam was conducted, and questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 121 publications
(264 reference statements)
0
3
0
Order By: Relevance
“…PR measures students' perception regarding the risk of the COVID-19 pandemic, including six items revised by Nguyen and Borazon [44]. For example, "I find COVID-19 has a high infection rate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PR measures students' perception regarding the risk of the COVID-19 pandemic, including six items revised by Nguyen and Borazon [44]. For example, "I find COVID-19 has a high infection rate.…”
Section: Methodsmentioning
confidence: 99%
“…Several prior studies using PRT to explore human behavior in pandemics have indicated that the situation's severity is the main factor contributing to protection motivation and the subsequent adoption of avoidance behavior. The negative effects of public relations are frequently highlighted in consumer behavior studies, such as in the context of travel [42], mobile financial services [43], and e-government [44]. In the context of online learning, Doan [14] has also indicated that PR fosters students' online learning intentions because school attendance puts students in direct contact with many people, which increases their chances of contracting COVID-19.…”
Section: Perceived Risk Online Learning Belonging and Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…GS is also considered a form of OS at a higher organisational level, and this support similarly promotes and enhances users' intention toward technology adoption (Hutahaean et al, 2023;Nguyen & Borazon, 2022;Stephan et al, 2015). Therefore, its effect mechanism on users' intention towards new technology adoption may also be explained by the OST.…”
Section: Inclusive Leadership Organisational Innovative Climate and I...mentioning
confidence: 99%
“…Therefore, its effect mechanism on users' intention towards new technology adoption may also be explained by the OST. GS in Vietnam was employed to evaluate policies, regulations, and supports of the Vietnamese government, which influenced and increased the number of users and determined whether or not these regulations affected their new technology adoption (Nguyen & Borazon, 2022). When laws, policies, and regulations are obligatory in a legal environment, everyone is required to abide by them.…”
Section: Inclusive Leadership Organisational Innovative Climate and I...mentioning
confidence: 99%